The Application of a Sodium Benzoate Salt-Nucleating Agent in Recycled Polyethylene Terephthalate: Crystallization Behavior and Mechanism - Meizhen Wang; Fuhua Lin; Tianjiao Zhao; Yapeng Dong; Xinyu Hao; Dingyi Ning; Yanli Zhang; Kexin Zhang; Dan Zhou; Jun Luo; Xiangyang Li; Bo Wang (Molecules)
The molecular chains of recycled polyethylene terephthalate (rPET) show breakage during daily use, causing poor crystallization and leading to mechanical properties that, when blended with the nucleating agent, become an effective method of solving this problem. The salt-nucleating agent sodium benzoate (SB), disodium terephthalate (DT), and trisodium 1,3,5benzene tricarboxylic (TBT) were synthesized, and an rPET/nucleating agent blend was prepared. The intrinsic viscosity (η) results showed that the η of the rPET/SB was decreased, which indicated the breakage of the rPET molecular chains. The FTIR results indicated that a chemical reaction occurred between the rPET and Na+ of the SB. Moreover, the Na+ content of the DT and TBT were higher than that of the SB, which increased the opportunity for low-molecular-weight rPET to reattach to the organic carboxylic acid portion of the nucleating agent, thereby increasing the η of the rPET/DT and rPET/TBT. The salt-nucleating agent sodium benzoate greatly improved the crystallization properties of the rPET, resulting in the half-crystallization time decreasing, the crystallization temperature increasing, and the effect of SB being better than that of DT and TBT. This was because the nucleating agent caused chemical nucleation with rPET, and the ionic groups acted as nucleation sites, while the rPET/DT and rPET/TBT, which had high molecular weights, hindered the improvement of the crystallization properties. The mechanical properties prove that the rPET/SB decreased due to the severe degradation of the rPET molecular chains. The mechanical properties of the rPET/DT and rPET/TBT were effectively improved because of the nucleating agent refining the grain size of the rPET and the high molecular weight. But the stacking of multitudinous rPET molecular chains can form a structure resembling physical cross-linking, causing a slight decrease in the mechanical properties of the rPET/TBT compared to the rPET/DT.